Third generation biofuels from microalgae - Dragone, Giuliano (2010)
Biofuel production from renewable sources is widely considered to be one of the most sustainable alternatives to petroleum sourced fuels and a viable means for environmental and economic sustainability. Microalgae are currently being promoted as an ideal third generation biofuel feedstock because of their rapid growth rate, CO2 fixation ability and high production capacity of lipids; they also do not compete with food or feed crops, and can be produced on non-arable land. Microalgae have broad bioenergy potential as they can be used to produce liquid transportation and heating fuels, such as biodiesel and bioethanol. In this review we present an overview about microalgae use for biodiesel and bioethanol production, including their cultivation, harvesting, and processing. The most used microalgal species for these purposes as well as the main microalgal cultivation systems (photobioreactors and open ponds) will also be discussed.